Lost generations : a boy, a school, a princess - Rath, J. Arthur (University of Hawaii Press, 2006)
Rath entered Kamehameha Schools as an eighth-grade boarder. This book is the story of his love affair with the school. It is also the story of Rath's recent battle, together with other alumni, for the integrity of his beloved Kamehameha against the school's trustees and their organization, the powerful Bishop Estate.